Net capital stock and capital productivity for China and regions: 1960 - 2005. An optimal consistency method - Jose Miguel Albala-Bertrand; Hao Feng (Queen Mary University of London, Department of Economics, 2007)
This analysis is based on the optimal consistency method (OCM) proposed by Albala-Bertrand (2003), which enables to estimate a capital stock for a benchmark year. This method, in contrast to most current approaches, pays due regards both to potential output and to the productivity of capital. From an initial OCM benchmark estimate, we produce series for the net capital stock, via a perpetual inventory method (PIM), for all China and some useful regional disaggregations over the 45-year period 1960-2005. As a by-product, we also make available the optimal productivities of incremental or marginal capital, corresponding to the net accumulated GFCF over 5-year sub-periods from 1960 onwards. We then attempt some structural analysis, showing that the quantity of resources rather than their quality appears to be largely behind growth rates, especially since the 1990s.
Keywords: O4; B4; E2; 330; China; Benchmark capital; Perpetual Inventory Method (PIM); Potential output; Capital productivity; Optimal Consistency Method (OCM); Structural analysis; Gesamtwirtschaftliches Anlageverm\~AƒÂgen; Investition; Kapitalproduktivit\~AƒÂt; Wirtschaftspotenzial; Regionale Wirtschaftskraft; China